Bilateral optic nerve head drusen with chorioretinal coloboma in the right eye - Ali Reza Dehghani; Leila Rezaei; Heshmatollah Ghanbari (Advanced Biomedical Research, 2016)
Chorioretinal coloboma is a congenital defect of the eye caused by improper closure of the embryonic fissure. Optic nerve head drusen (ONHD) are white calcareous deposits that are generally asymptomatic. We report a very rare association of both in a healthy patient with no any systemic syndrome. A 16-year-old man was referred to our clinic from suffering blurred vision. Best corrected visual acuity of the right eye was 6/10 and 10/10 in the left one. External ocular and slit lamp examination were normal. Dilated ophthalmoscopy showed marked swelling in both optic nerves and chorioretinal coloboma in the right eye inferiorly. Ultrasonography showed an echodense structure with acoustic shadowing in both eyes consistent with buried ONHD. Visual field testing showed normal field in the left eye and moderate superior field depression in the right eye corresponding to inferior coloboma in funduscopy. Results of general medical and neurologic, cardiologic, and other examinations were normal. To the best our knowledge combination of bilateral ONHD and unilateral chorioretinal coloboma in a healthy patient with no any systemic syndrome has not been published in the literature. We reported this very rare association and recommended examine eyes and other body organs. In such cases that coloboma is associated with ONHD, we should keep in mind Noonan syndrome. The diagnosis of Noonan syndrome is clinical and confirm by the consultant pediatricians and clinical geneticists.